Manajemen Pembelajaran PJOK PTM Terbatas SMP Di Kecamatan Kalinyamatan Kabupaten Jepara Tahun 2021 (Indonesian Journal for Physical Education and Sport, 2022)
This research background is the changing of the learning system from e-learning to limited face-to-face learning. This limited face-to-face learning has an effect on learning management, especially on Physical Education class. The purpose of this research is to find out how the learning management for Junior High Schools’s Physical Education in Kalinyamatan District, Jepara Regency with limited face-to-face learning. This research uses a quantitative descriptive method with data collection technique using a questionnaire instrument. The population of this research were all PE Junior High School Teachers in Kalinyamatan District, Jepara Regency, the total sample of this research are 9 teachers. The data are analyzed using descriptive statistics technique and the data results elaborated using descriptive percentages. The results of this research showed the value of the planning indicator obtained an average value of 13.67 and categorized as effective and efficient, the organizational indicator obtained an average value of 12.78 and categorized as a quite effective and efficient, the actuanting indicator obtained an average value of 12.67 and categorized as a fairly effective and efficient, the evaluation/controlling indicator obtained an average value of 9.33 and categorized as a less effective and efficient, the overall average value of the indicator is 12.11 and categorized as a quite effective and efficient. The conclusion from the research of the limited face-to-face physical education management learning for Junior High Schools in Kalinyamatan District, Jepara Regency can be categorized as quite effective and efficient from the indicators of planning, organizing, actuanting, and evaluating. With this result, teachers need to improve their skills in teaching to create a pleasant learning atmosphere for students.